2013
DOI: 10.3109/17435390.2013.869627
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-dependent silver nanoparticle uptake and transformation by Atlantic killifish (Fundulus heteroclitus) embryos

Abstract: We assessed the biodistribution and in situ speciation of sub-lethal concentrations of citrate-coated silver nanoparticles and dissolved silver within Fundulus heteroclitus embryos. Using a thorough physico-chemical characterization, we studied the role of salinity on both uptake and in situ speciation. The Ag uptake or adsorption on the chorion was reduced by 2.3-fold for Ag NPs, and 2.9-fold for AgNO3 in estuarine water (10‰ ASW) compared to deionized water (0‰ ASW). Between 58% and 85% of the silver was loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
5
24
0
Order By: Relevance
“…1a, Ag-NPs strongly associate with the chorion and substantial amounts seem to reach the PVS, whereas only minor amounts reach the embryo. A high sorption of Ag-NPs to the chorion structure was previously reported and quantified by Auffan et al (2014) 28 with a percentage of 58 to 85% Ag-NPs accumulating at the chorion after 48 h of exposure to 5 mg l −1 Ag-NPs. Ionic silver stemming from the AgNO 3 solution was predominantly located in the PVS and to a lesser extent in the chorion (Fig.…”
Section: Distribution Of Nps and Metals In Different Zfe Compartmentssupporting
confidence: 58%
See 1 more Smart Citation
“…1a, Ag-NPs strongly associate with the chorion and substantial amounts seem to reach the PVS, whereas only minor amounts reach the embryo. A high sorption of Ag-NPs to the chorion structure was previously reported and quantified by Auffan et al (2014) 28 with a percentage of 58 to 85% Ag-NPs accumulating at the chorion after 48 h of exposure to 5 mg l −1 Ag-NPs. Ionic silver stemming from the AgNO 3 solution was predominantly located in the PVS and to a lesser extent in the chorion (Fig.…”
Section: Distribution Of Nps and Metals In Different Zfe Compartmentssupporting
confidence: 58%
“…26,27 A barrier function of the chorion was likewise reported for several other NPs, namely Ru@SiO 2 particles (60, 200 nm), 17 as well as CuO-, ZnO-, Co 3 O 4 -, and NiO-NPs (all NPs with a primary particle size of 20-50 nm). 18 Furthermore, Auffan et al (2014) 28 concluded that the chorion acts as a protective membrane limiting the internalization of NPs as well as metal cations.…”
Section: Introductionmentioning
confidence: 99%
“…The 96-h LC50s of ZnO-NPs for the marine copepod Tigriopus japonicus were 1.22 mg/L and 2.44 mg/L at salinities of 5 and 35 ppt, respectively 8 . After exposure to citrate-coated silver nanoparticles (5 mg/L) for 48 h, uptake of silver by embryos of the Atlantic killifish Fundulus heteroclitus was more than 2-fold greater in freshwater (0 PSU) than in brackish water (10 PSU) 36 . Consistent with the results presented here, results of another study showed that the 96-h IC50s of ZnO-NPs to T .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we decided to look further into the mechanisms of toxicity occurring at higher salinity (15 psu and 30 psu). Based on Auffan et al [10], we hypothesized that at such a salinity (15-30 psu), Ag bioaccumulation would be different compared with freshwater because of varying dissolution rates as a function of salinity [11]. Experimental evidence also shows that dissolved Ag is less bioavailable at higher salinities than at lower ones, mainly because of differences in dissolved Ag speciation between salinities [12].…”
Section: Introductionmentioning
confidence: 98%